1994
DOI: 10.1002/pro.5560031102
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor: Structure/function relationships

Abstract: Nerve growth factor (NGF), which has a tertiary structure based on a cluster of 3 cystine disulfides and 2 very extended, but distorted 0-hairpins, is the prototype of a larger family of neurotrophins. Prior to the availability of cloning techniques, the mouse submandibular gland was the richest source of NGF and provided sufficient material to enable its biochemical characterization. It binds as a dimer to at least 2 cell-surface receptor types expressed in a variety of neuronal and non-neuronal cells. Residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 86 publications
2
37
0
Order By: Relevance
“…Many efforts have been devoted to design mimetics using NGF fragments. Crystallographic and molecular modeling studies of NGF/TrkA complexes (McDonald et al, 1991;McDonald and Chao, 1995;Urfer et al, 1998;Wiesmann et al, 1999), mutagenesis analysis (Ibànez et al, 1992;Kahle et al, 1992;Drinkwater et al, 1993;Shih et al, 1994;Woo et al, 1995;Krüttgen et al, 1997;Kullander et al, 1997;Rydén and Ibàñez, 1997), and chemical modification of specific amino acids (Bradshaw et al, 1994;McDonald and Chao, 1995) have indicated the hydrophilic loops 1 and 4 and the N-terminal region of NGF as the most relevant for its biological activity. Among various peptides reported in the literature, linear peptides showed inhibitory, but no agonist activity (Longo et al, 1990), and cyclic peptides corresponding to the loop 1 sequence were shown later to have a 10-fold higher inhibitory activity (LeSauteur et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been devoted to design mimetics using NGF fragments. Crystallographic and molecular modeling studies of NGF/TrkA complexes (McDonald et al, 1991;McDonald and Chao, 1995;Urfer et al, 1998;Wiesmann et al, 1999), mutagenesis analysis (Ibànez et al, 1992;Kahle et al, 1992;Drinkwater et al, 1993;Shih et al, 1994;Woo et al, 1995;Krüttgen et al, 1997;Kullander et al, 1997;Rydén and Ibàñez, 1997), and chemical modification of specific amino acids (Bradshaw et al, 1994;McDonald and Chao, 1995) have indicated the hydrophilic loops 1 and 4 and the N-terminal region of NGF as the most relevant for its biological activity. Among various peptides reported in the literature, linear peptides showed inhibitory, but no agonist activity (Longo et al, 1990), and cyclic peptides corresponding to the loop 1 sequence were shown later to have a 10-fold higher inhibitory activity (LeSauteur et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant substitution studies indicated that residues Lys 32 and Lys 34 (17) and other residues (18) are likely to interact with p75 receptors. The NGF sites interacting with TrkA have also been derived via chemical modification (11,19,20), recombinant protein (18, 20 -23), and NGF-TrkA co-crystallization approaches (24). Taken together, these studies indicate that TrkA binding sites consist of residues in NGF loop 2 (residues 40 -49), loop 4 (residues 91-97), the N terminus (residues [1][2][3][4][5][6][7][8], and the C terminus (residues 111-115).…”
mentioning
confidence: 99%
“…Multiple techniques have been used to deduce which domains of the NGF protein interact with NGF receptors (11). A peptide mapping approach in which synthetic peptides with sequences corresponding to specific NGF regions were tested for their ability to inhibit NGF activity pointed to residues 29 -35 as a key active site (12).…”
mentioning
confidence: 99%
“…A first approach used chemical modification of NGF where residues receptive for different agents could be blocked and the effect analyzed (for review, see Ref. 19). Enzymatic cleavage of NGF has identified the NH 2 terminus to be critical for binding to TrkA (20 -22).…”
mentioning
confidence: 99%